ANALISIS KONSUMSI HIDROGEN PADA PENCAIRAN BATUBARA BANKO TENGAH DAN RESIDU KILANG MINYAK BALIKPAPAN - Hartiniati, Hartiniati (Badan Pengkajian dan Penerapan Teknologi, 2007)
A series of liquefaction test to understand the effect of initial hydrogen pressureon the yield structure of Banko coal liquefaction under the presence of catalystand short residue solvent was studied. Three sets of initial pressure at 5, 9 and12MPa were tested under liquefaction condition. The test was carried out in CoalLiquefaction Laboratory-BPPT, using 1 liter autoclave at temperature of 450oC forone hour. The results showed that by increasing the initial H2 pressure from5MPa to 9 and 12MPa would improve the distillate yield for about 8-9wt%dafc.This was due to the availability of hydrogen gas provided at 5MPa was smallerthan 9MPa and 12MPa, so that the molecular hydrogen transformed into protonhydrogen and involved in stabilizing decomposed coal structure and shortresidue became larger. It was found that the changes of H2O, CO+CO2 and ofC1 C4 yields were independent to the variable of initial hydrogen pressure. Theseresults possibly confirm that H2O and CO+CO2 yield depend on the raw coalquality input. It was also found that at higher initial pressure ( 9MPa), thehydrogen consumption was become less. This may confirm that hydrogen donoravailability of short residue at higher pressure plays a good role in the reaction sothat less amount of hydrogen from the gas is required for the liquefactionreaction.Kata kunci: hydrogen-donor, catalyst, liquefaction yield